Optimizing Tourism Promotion for Situ Bagendit Through Innovation in a Web-Based Virtual Tour Application - Sri Rahayu; Syahrul Yanuar; Yosep Bustomi (Teknika, 2024)
Situ Bagendit is a well-known natural lake tourist destination in Garut, West Java. However, information about Situ Bagendit is still difficult for the public to access. Information is often spread by word of mouth and social networks, which highlights the need for more effective promotional media. This research aims to create a virtual tour to promote Situ Bagendit and address the issue of information accessibility for tourists. The application was developed using the Multimedia Development Life Cycle (MDLC) method, utilizing VR technology and 3DVISTA software, and incorporating images and videos captured with a mobile or 360° camera. The application is hosted on Instagram, featuring interactive elements such as chat and location information via Google Maps. The research findings indicate that the virtual tour application was successfully built with features like a gallery, videos, information, WhatsApp, and Google Maps. It received a score of 80.25 on the System Usability Scale (SUS), earning an "Excellent" rating and falling within the "Acceptable" category. This application is expected to increase tourist interest in visiting Situ Bagendit.